PENGEMBANGAN BAHAN AJAR KETERAMPILAN MENULIS TEKS NARASI BERBASIS MODEL BRAINWRITING DAN MEDIA KOMIK UNTUK SISWA KELAS IV SEKOLAH DASAR - Yawuru Nur Hasanah; Chandra; Elfia Sukma; M. Habibi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop narrative writing teaching materials based on the Brainwriting model and comic media for fourth grade elementary school students using the Plomp development model. The development process consisted of three stages, namely preliminary research, prototyping phase, and assessment phase. The preliminary research stage was conducted through needs analysis, curriculum analysis, and student characteristic analysis. The prototyping phase included designing, developing, validating, and revising the teaching materials through formative evaluation. The assessment phase was carried out to determine the practicality and effectiveness of the developed teaching materials. The research subjects consisted of fourth grade elementary school students and teachers in Padang City. Data collection techniques included observation, interviews, validation sheets, practicality questionnaires, and learning outcome tests. The results showed that the teaching materials developed were categorized as valid based on expert validation, practical based on teacher and student responses, and effective in improving students’ narrative writing skills. Therefore, the teaching materials based on the Brainwriting model and comic media are suitable for use in learning narrative writing in elementary schools.